Pengaruh Profitabilitas, Pertumbuhan Perusahaan, dan Solvabilitas Terhadap Harga Saham Farmasi yang Terdaftar di BEI - Adelia Eka Safitri; Detak Prapanca; Wisnu Panggah Setiyono (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze and understand the effect of profitability, company growth, and solvency on the stock prices of pharmaceutical companies listed on the Bursa Efek Indonesia during the 2022–2024 period. Profitability is proxied by Return on Assets (ROA), company growth is measured by Growth, and solvency is measured by the Debt to Asset Ratio (DAR). This research employs a quantitative method using purposive sampling techniques and obtains a sample of 10 pharmaceutical companies, with data analysis conducted using EViews 12. The results indicate that profitability, company growth, and solvency each have a positive and significant effect on stock prices. The findings suggest that an increase in ROA reflects the company’s effectiveness in generating profits, thereby enhancing investor confidence and driving stock price increases; high company growth signals strong future business prospects, attracting investor interest; and solvency, as reflected by DAR, demonstrates the company’s ability to optimally manage its capital structure, providing a positive signal to the market as long as debt levels remain within reasonable limits. Simultaneously, these three variables significantly contribute to explaining stock price movements of pharmaceutical companies during the research period.